Daily Carnosine and Anserine Supplementation Alters Verbal Episodic Memory and Resting State Network Connectivity in Healthy Elderly Adults - Rokicki, Jaroslav; Li, Lucia; Imabayashi, Etsuko; Kaneko, Jun; Hisatsune, Tatsuhiro; Matsuda, Hiroshi (Frontiers in Aging Neuroscience, 2015)
Carnosine and anserine are strong antioxidants, previously demonstrated to reduce cognitive decline in animal studies. We aimed to investigate their cognitive and neurophysiological effects, using functional MRI, on humans. Thirty-one healthy participants (age 40-78, 10~male/21~female) were recruited to a double-blind placebo-controlled study. Participants were assigned to twice-daily doses of imidazole dipeptide formula ($n = 14$), containing 500~mg (carnosine/anserine, ratio 1/3) or an identical placebo ($n = 17$). Functional MRI and neuropsychological assessments were carried out at baseline and after 3 months of supplementation. We analyzed resting state functional connectivity with the FSL fMRI analysis package. There were no differences in neuropsychological scores between the groups at baseline. After 3 months of supplementation, the carnosine/anserine group had better verbal episodic memory performance and decreased connectivity in the Default Mode Network, the Posterior Cingulate Cortex and the Right Fronto Parietal Network, as compared with the placebo group. Furthermore, there was a correlation between the extents of cognitive and neuroimaging changes. These results suggest that daily carnosine/anserine supplementation can impact cognitive function and that network connectivity changes are associated with its effects.